2019
DOI: 10.17576/ajag-2019-11-06
|View full text |Cite
|
Sign up to set email alerts
|

Does Political Connection Moderate Women Directors’ Effect on CSR Disclosure? Evidence from Malaysia

Abstract: The objectives of this paper are: to examine the moderating effect of government ownership on the relationship between women directors and corporate social responsibility (CSR) disclosure; and to study the moderating effect of politicians on boards on the relationship between women directors and corporate social responsibility (CSR) disclosure. This paper gathered information from companies' annual reports for the year 2013. From a sample of 300 non-financial companies listed on Bursa Malaysia, this paper foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 39 publications
1
8
0
4
Order By: Relevance
“…To create a good image of the company, the board may hide damaging information and magnify more useful information in CSR disclosure. Most of the prior studies found a negative impact of political connection on the quality of CSR disclosure (Rahman, Jamil, & Ismail, 2019). The political board members are less willing to follow the rules regarding equal employment, environmental policies, and regulative policies.…”
Section: Political Board Member and Csrdmentioning
confidence: 97%
“…To create a good image of the company, the board may hide damaging information and magnify more useful information in CSR disclosure. Most of the prior studies found a negative impact of political connection on the quality of CSR disclosure (Rahman, Jamil, & Ismail, 2019). The political board members are less willing to follow the rules regarding equal employment, environmental policies, and regulative policies.…”
Section: Political Board Member and Csrdmentioning
confidence: 97%
“…Salah satu faktor yang dapat meningkatkan jumlah pengungkapan tanggung jawab sosial adalah jumlah direksi wanita dalam perusahaan (Maiza, 2019). Keragaman dewan, khususnya keragaman gender dewan, telah mendapat perhatian yang signifikan dari badan pengatur di banyak negara dan menjadi perhatian global berkelanjutan (Al Fadli et al, 2019).…”
Section: Landasan Teori a Direktur Wanitaunclassified
“…Keragaman dewan, khususnya keragaman gender dewan, telah mendapat perhatian yang signifikan dari badan pengatur di banyak negara dan menjadi perhatian global berkelanjutan (Al Fadli et al, 2019). Maiza (2019) mengemukakan bahwa terdapat beberapa studi tentang direktur wanita dan literatur yang kuat namun masih mungkin adanya keragaman dalam komposisi dan sikap mereka terhadap isu-isu tertentu, pemantauan dan proses pengambilan keputusan.…”
Section: Landasan Teori a Direktur Wanitaunclassified
See 1 more Smart Citation
“…The existent literature documented that firms in both developing and developed economies are deliberately attempting to integrate themselves into political organizations (Boubakri et al , 2008; Jia, 2016; Rauf et al , 2021; Rauf et al , 2020; Zheng et al , 2015; Qian and Chen, 2021; Rahman et al , 2019). However, it is still unclear how political connection affects firm CSR disclosure in a meaningful way.…”
Section: Introductionmentioning
confidence: 99%